Cotransport of micro- and nano-plastics with chlortetracycline hydrochloride in saturated porous media: Effects of physicochemical heterogeneities and ionic strength. (1st February 2022) - Xu, Lilin; Liang, Yan; Liao, Changjun; Xie, Tian; Zhang, Hanbin; Liu, Xingyu; Lu, Zhiwei; Wang, Dengjun
Highlights: MNPs and CTC inhibit each other's transport potential when coexist. Presence of CTC tends to increase MNPs aggregation and thus enhances retention. Soil colloids have different effects on the single- and co-transport of CTC and MNPs. Physicochemical heterogeneities greatly influence the cotransport of CTC and MNPs. A larger MNPs fraction increases the potential on adsorption-cotransport with CTC. Abstract: Global production and use of plastics have resulted in the wide dissemination of micro- and nano-plastics (MNPs) to the natural environment. Potentially acting as a vector, the role of MNPs on the fate and transport of environmental pollutants (e.g., antibiotics such as chlortetracycline hydrochloride; CTC) has garnered global concern recently. Herein, the cotransport of MNPs and CTC in columns packed with uncoated sand or soil colloid-coated sand (SCCS) under different degrees of physicochemical heterogeneity and ionic strength was systematically explored. Our results show that MNPs and CTC inhibit the transport of each other when they coexist. The adsorption of CTC onto sand grains, soil colloids, and MNPs, as well as the aggregation of MNPs in the presence of CTC could be the major contributors to the enhanced retention of CTC and MNPs. In SCCS with different degrees of soil colloid coating, the adsorption of CTC on soil colloids is critical to influence the transport of CTC, and the nonlinear retention of MNPs to soil colloids is mainly attributed to the alteration of collector surface roughness by soil colloids. High ionic strength slightly facilitates CTC transport due to the competition for adsorption sites and the formation of CTC macromolecules, but significantly inhibits MNPs transport by suppressing the electrostatic double layers based on colloid stability theory. Consequently, the cotransport of MNPs and CTC is governed by the coupled interplay of collector surface roughness and chemical heterogeneity, due to the soil colloid coatings and the adsorbed CTC on the surfaces associated with solution chemistries such as ionic strength. Increased cotransport of MNPs and CTC occurred under a higher concentration of MNPs due to a larger number of adsorption sites for CTC. Our findings advance the current understanding of the complex cotransport of MNPs and antibiotics in the environment. This information is valuable for understanding contaminant fate and formulating strategies for environmental remediation due to the contamination of MNPs and co-occurring contaminants. Graphical abstract: Image, graphical abstract